Cabaran, Impak dan Strategi Pelaksanaan Pembelajaran dan Pengajaran dalam Talian Terhadap Kesihatan Mental Pelajar dan Pensyarah Kolej Komuniti: Challenges, Impacts, and Strategies of Online Learning on Mental Health of Community College Students and Lecturers - Ealangov, Suganti; Kadir, Irman Fareed; Zakaria, Nur Asyifa; Soppy, Anis Humaira’; Mahamod, Zamri (Online Journal for TVET Practitioners, 2022)
The COVID-19 pandemic has made a significant impact on almost all sectors of the economy including the education sector. In addition, the drastic closure of educational institutions and transition from conventional learning to online have affected students and educators, especially in terms of mental health. The purpose of this study was to explore the challenges, impacts, and strategies of online learning on the mental health of students and Community College lecturers. This study was conducted using the case study method. The data collection was conducted by interviewing five students and five community college lecturers. Partially structured interview instruments adapted from recent studies are used for data collection purposes. The findings show that the internet, environment, competence, and workload are among the challenges faced by students and lecturers that impact on mind, psychology, physical, and behavior. Following that, informants also outlined various strategies taken to ensure that mental health is at an optimum level during pandemics. In conclusion, online learning has an impact on the mental health of students and lecturers, but this impact is not significant and can be kept controlled by spiritual approaches, doing favourite activities, sports, and leisure.